2012
DOI: 10.1126/science.1224198
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Prolonged Postreproductive Life Span in Killer Whales

Abstract: Killer whale mothers continue to help their adult male offspring to survive long after ceasing reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
174
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(186 citation statements)
references
References 6 publications
10
174
2
Order By: Relevance
“…There is mounting evidence that menopause evolved via inclusive fitness benefits gained by helping kin; both postreproductive humans [11][12][13][14] and killer whales [15] increase the reproductive success and/or survival of their relatives. But how postreproductive females help their kin remains enigmatic.…”
Section: Resultsmentioning
confidence: 99%
“…There is mounting evidence that menopause evolved via inclusive fitness benefits gained by helping kin; both postreproductive humans [11][12][13][14] and killer whales [15] increase the reproductive success and/or survival of their relatives. But how postreproductive females help their kin remains enigmatic.…”
Section: Resultsmentioning
confidence: 99%
“…Household resources in part generated by sisters are used to feed brothers, as we have shown that brothers can be a cost to their sisters. Interestingly, in killer whales, mothers are thought to support sons for this reason and sons have been observed to die at a much higher rate once their mothers are gone [26,31] ( perhaps because sisters have less reproductive interest in their brother's fitness than do their mothers). It remains to be seen whether Mosuo males do worse after their mother dies, but we did note that older males do sometimes leave their natal residence to join their wives' households later in life [5].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pilot whales are organised in closed matrilineal units, similar to killer whales, for which the rearing of young animals and the interaction between the related individuals seem to play a major role in structure and dynamics (Amos et al 1991, de Stephanis et al 2008b. The deaths of killer whale mothers directly affect the survival of their offspring, even long after weaning (Foster et al 2012). Therefore, these potential additive deaths caused indirectly by the epizootic likely compensate the bias.…”
Section: Discussionmentioning
confidence: 99%